Providing for the independence of the judiciary in Africa: a quest for the protection of human rights - Akonumbo, Atangcho Nji (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2003.